Object detection and recognition based on YOLOv11 - Rodiuk , A. I; Nikolyuk , P. K. (Прикладні аспекти сучасних міждисциплінарних досліджень, 2026)
The paper is devoted to the problem of object detection and recognition using the YOLOv11 model. The paper discusses technical improvements to the architecture and analyzes the effectiveness of the model in different conditions and on complex images.